FIQH MASHALIHUL MURSALAH DALAM PERSPEKTIF MAQÂSHID SYARÎ’AH: FIQH MASHALIHUL MURSALAH - Nurkholis; Muhammad Wisnu Khumaidi; Singgih, Muhammad (An Naba, 2018)
Islam is a comprehensive and universal religion, because its teachings cover aspects of theology and humanism. Islam is not an arrogant / egocentric religion that only requires each adherent to glorify its creator, but furthermore Islam exists to lift human dignity and dignity. Various problems in Islam, Islam provides the best solution which is then translated through its shari'ah according to the masses and conditions in realizing the Shari'a and its laws as indicated in the Qur'an وماجعل عليكم في الدين من حرج (and He never made it for you in religion narrowness). In other words, Islam requires the creation of the benefit of all mankind without exception. The concept of maslahat becomes interesting for us to map because there are many wild understandings of this theory related to solving a law that is not interpreted by the Qur'an textually so that it raises pros and cons not only among contemporary intellectuals but, salaf scholars first was not free from debatable about the concept and fiqh of this benefit. To map the concept of maslahatul mursalah, of course we must explore in detail about one of these mukhtalaf (arguments argued) with a persuasive approach to many things that are questions from the theory of this problematic maslahatul. Does Islam accommodate the problem of this problem as mashodirut tasyri '(source of law), what is the object / target of the problem, how is the law practiced by using the problem of the problem and many more problems that we must explain so that it does not appear to be the problem that sets the context (maqasid) and leaving the text because it is often used as a shield by the privatization of Islam which reduces the texts of the Qur’an by resting on the concept of this benefit.